Darfur: Livelihoods Under Seige - Young, Helen; Osman, Abdul Monim; Aklilu, Yacob; Dale, Rebecca; Badri, Babiker; Fuddle, Abdul Jabbar Abdullah (Tufts Archival Research Center, 2005)
It is almost two years since the beginning of the rebel insurgency in Darfur, but the Conflict, Armed (War) continues, the ceasefire has been frequently violated, and the world's worst humanitarian crisis continues to deepen. At the last estimate, more than 1.6 million people had been displaced as a result of systemÂatic attacks on villages, with associated violence, killings, burning of homes, looting of Livestock, and theft and destruction of material assets.